Dielectric Properties of Nd-Doped Yttrium Iron Garnet and Cu Or Co-Doped Nickel Zinc Ferrites - Khe, Cheng Seong (2006)
In this work, three series of soft ferrites were synthesized via solid state route. These are Nio.3-xCu,Zno.7Fe20(4x = 0.0, 0.05, 0.10, 0.15, 0.20, 0.25 and 0.30), Ni0.S- .C&Zno.~Fe204 (x=O.O, 0.1, 0.2, 0.3, 0.4, and 0.5) and Y3..NdxFes0~2 (x=O.O, 0.4, 0.8, 1.2 and 1.6). The X-ray diffraction patterns showing single phases for these three samples series, confirmed that the spinel and garnet structure had been formed in the Ni-Zn ferrites and YIG respectively. Ni-Zn ferrites substituted with copper oxide showed exaggerated grain growth whereas the other series substituted with cobalt oxide had no massive changes in the microstructure. For the YIG substituted with neodymium oxide, the first sample exhibited a porous microstructure and developed to become a more compact and poreless microstructure as neodymium increased. Measurement of the electrical properties was carried out in the temperature range from 28°C to 300°C in the low frequency region of 10 Hz to 1 MHz. Impedance analyzer was employed in the ac data acquisition whereas a pico-ammeter and a dc voltage source were used to measure electric current at different voltages. The results obtained from dielectric measurements indicate that microstructure of the samples plays an important role in the dielectric dispersion. A sample with higher porosity is associated with a low value of dielectric permittivity due to its high resistivity. Meanwhile a sample with a more compact structure exhibits higher dielectric permittivity due to its higher conductivity. Hence, electron hopping between ~ ean~d ~+e w~ou'ld increase in the conductive sample and give higher dielectric permittivity if compared with the resistive one. The dielectric response for every sample in the three series of soft ferrites displayed different mechanisms throughout the investigated temperature range. Therefore, dielectric behaviour of a sample can be modeled into at least two equivalent circuits. The complex impedance plots of both samples Ni-Zn ferrites and YIG showed overlapping semicircles. However, at high temperature the high frequency arc disappeared and there remained just one semicircle. The center of the semicircle for all samples was depressed below the real impedance axis and described by the parameter a. The results indicate that all these three series of soft ferrites can be represented by two parallel RC circuits connected in series that correspond to the contributions of grain and grain boundary. The ac conductivity for the three series of soft ferrites showed almost similar behaviour. At lower temperature, the ac curves can be divided into two region. The low frequency region showed that the ac conductivity was weakly dependent on frequency whereas at high frequency region, it was strongly dependent on frequency. As the temperature increased, the ac conductivity seemed independent of frequency. Extrinsic and intrinsic conductions had been inferred to occur in these samples. It is also found that microstructural entities such as grains and porosity play an important role in the dc resistivity. The two activation energies obtained indicated that there were probably two parallel conduction mechanisms or spin reorientation phase transition occurred.